Universitas Baghdad dan Kajian Islam; Pendidikan Gratis di Tengah Masa Sulit - Pungki Purnomo (Buletin Al-Turas, 2005)
Though recently experiencing the difficult political conditions, Iraqi's government consistently puts emphasis on improving its national education. This attitude is reflected, for example, from its grants in the funding scholarship programs for the people both in Iraq and abroad. Moreover, the government also grants scholarships for non-Iraqi citizens, including Indonesians, in the country's universities.